KELEMBAGAAN PETANI DAN SOSIAL EKONOMI TERHADAP PARTISIPASI ANGGOTA KELOMPOK DALAM PROGRAM PENGEMBANGAN USAHA PANGAN MASYARAKAT (PUPM) - Euis Dasipah; Karyana KS; Rina Ridiawaty (Universitas Galuh Ciamis, 2021)
Community participation is important in the successful implementation of the Community Food Business Development (PUPM) program. This study aims to (1) Assess the effect of group management on the participation of farmer group members in program activities; (2) Assessing the socioeconomic influence on the participation of farmer group members in program activities; (3) Assess the influence of farmer institutions and socioeconomic on the participation of farmer group members in the success of the Community Food Business Development (PUPM) program. Descriptive Analysis research methods. Data collected by sampling technique. The sampling method used was simple random sampling. The study population numbered 138, with a research sample of 102 people. The selection of sample districts is done deliberately because the kecamatan is a location that receives a Community Food Business Development (PUPM) program. The results showed that the Institutional Factors of farmers had a positive and significant contribution to the level of participation of farmer group members in the Community Food Business Development (PUMP) program. Socio-economic factors of farmers have a positive and significant contribution to the level of participation of farmer group members in the Community Food Business Development (PUMP) program. Simultaneously farmer Institution and farmer socioeconomic contributed significantly to the participation of farmer group members in the Community Food Business Development (PUMP) program.